2013
DOI: 10.1007/s00216-013-7121-9
|View full text |Cite
|
Sign up to set email alerts
|

Enantioseparation of 6-aminoquinolyl-N-hydroxysuccinimidyl carbamate tagged amino acids and other zwitterionic compounds on cinchona-based chiral stationary phases

Abstract: The fluorescent tag 6-aminoquinolyl-N-hydroxysuccinimidyl carbamate (AQC; AccQ Fluor reagent kit from Waters) is a commercial N-terminal label for proteinogenic amino acids (AAs), designed for reversed-phase separation and quantification of the AA racemates. The applicability of AQC-tagged AAs and AA-type zwitterionic compounds was tested for enantiomer separation on the tert-butyl carbamate modified quinine and quinidine based chiral stationary phases, QN-AX and QD-AX employing polar-organic elution condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Hellinger et al reported that interaction between AQC-AAs and QN-or QD-type CSPs can lead to great degrees of enantioseparation [25]. Because AQC-AA derivatives are more hydrophobic than N-Ac-AAs, we required larger MeOH contents in the mobile phase for their elution.…”
Section: Analyses Of Fluorescently Derivatized Chiral Amino Acidsmentioning
confidence: 98%
See 2 more Smart Citations
“…Hellinger et al reported that interaction between AQC-AAs and QN-or QD-type CSPs can lead to great degrees of enantioseparation [25]. Because AQC-AA derivatives are more hydrophobic than N-Ac-AAs, we required larger MeOH contents in the mobile phase for their elution.…”
Section: Analyses Of Fluorescently Derivatized Chiral Amino Acidsmentioning
confidence: 98%
“…This tendency well agreed with previous study on enantioseparation of AQC-AAs with commercial cinchona alkaloid type CSPs (Chiralpak QN-AX and QD-AX). Hellinger et al discussed that poor enantioseparation of acidic AAs (Asp and Glu) derivatives with cinchona alkaloid CSPs lies in ion pairing interaction between the acidic side chain and the anion exchange moieties of CSPs [25]. The additional acidic group in b-and g-position of Asp and Glu functions as a competitor to the a-carboxylic acid for ion pairing interaction with the quinuclidine amine.…”
Section: Analyses Of Fluorescently Derivatized Chiral Amino Acidsmentioning
confidence: 98%
See 1 more Smart Citation
“…26 Among them, liquid chromatography is the most widely used. Liquid chromatography is based on the modified silica gel material comprising either immobilized small molecules of chiral selectors (CSs; eg, Cinchona-based ion exchangers), 27 macromolecule CSs (eg, biopolymers or synthetic polymers), 28 or macrocyclic CSs (cyclodextrin antibiotics). 29 The broad family of CSPs has enabled separation of almost any racemic mixture of choice, ranging from neutral lipophilic to highly polar hydrophilic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…As the chiral stationary phase, an enantioselective column QN-AX (1.5 mm i.d. × 150 mm, 25 • C, 5 m) was used, which has been reported to separate the enantiomers of N-protected amino acids efficiently[34].The 6-MOQ-Ala enantiomers were nicely separated within 15 min (˛ = 1.16) using 0.02% FA in MeCN-MeOH (50:50, v/v) solution as a mobile phase (200 L/min). The value of LLOD using fluorescence detection was 50 fmol/injection, and that of MS/MS was 0.1 fmol/injection.…”
mentioning
confidence: 99%